PTU-122 Do the follow-up rates of positive hepatitis c screens vary depending on the source of the test?. (22nd June 2015) - On, W; Dale, S; Maheswaran, T; Karmo, M
Abstract : Introduction: The hepatitis C (HCV) treatment pathway usually begins with a HCV screen. In our hospital, a positive HCV screen is determined by an enzyme immunoassay that detects anti-HCV antibodies. If a patient is not known to have HCV, a further blood sample is required for quantifying HCV viral load and genotyping by polymerase chain reaction (PCR). A proportion of positive HCV screens are not followed up upon and it is the responsibility of the requesting clinician to arrange appropriate follow-up. We aimed to determine whether the follow-up rates of positive HCV screens vary depending on the source of the test. Method: A retrospective, single-centre evaluation over a 10 year period from January 2004 to September 2014 was carried out. Only patients with an address within the hospital's catchment area and over the age of 18 at the time of testing were included. The sources of the positive HCV screens were obtained from our hospital's laboratory database and divided into five groups: Inpatients (IP), outpatients excluding gastroenterology departments (OP), general practice (GP), maternity unit (MA) and community drug team (CM). We analysed whether these patients had follow-up PCR testing and whether they were referred to a gastroenterology clinic. Results: 348 patients with positive anti-HCV antibodies were identified. 227 patients (65.2%) had follow-up PCR testing done. The rates of subsequent PCR testing after a positive HCV screen were: CM (83.3%), GP (72.7%), OP (71.4%), MA (57.7%) and IP (46.1%) with significant differences between the groups (p < 0.001, ANOVA). 250 patients (71.8%) were referred to a gastroenterology clinic but 39 patients (11.2%) did not attend (DNA) their first appointment. The referral rates were: CM (84.9%), GP (78.8%), OP (74.3%), IP (58.9%) and MA (57.7%); (p < 0.001, ANOVA). PCR and referral outcomes are presented in the Table 1 . Conclusion: The follow-up rates of positive HCV screens vary depending on the source of the test. We postulate that the frequency of interactions between patients and healthcare professionals is a key factor in ensuring follow-ups. Better follow-up of HCV screening is needed in order to achieve better clinical outcomes for HCV. This is particularly important as more efficacious and tolerable drugs are becoming increasingly available. Disclosure of interest: None Declared.